Long-term effects of intrajejunal levodopa infusion on sleep in people with advanced Parkinson's disease - Diaconu, Ştefania; Irincu, Laura; Ţînţ, Diana; Falup-Pecurariu, Cristian (Frontiers in Neurology, 2023)
Background Sleep disturbances are commonly encountered in people with advanced Parkinson's disease (PD). In these stages, levodopa–carbidopa intestinal gel (LCIG) is recommended for improving motor symptoms, some non-motor dysfunctions, and quality of life in these patients. This study aimed to assess the effects of LCIG on sleep in PD in a longitudinal study. Study design An open-label observational study in patients with advanced PD undergoing LCIG treatment was carried out. Measures and outcomes In total, 10 consecutive advanced people with PD were evaluated at the baseline and after 6 months and 1 year, respectively, of LCIG infusion. Sleep parameters were assessed with several validated scales. We assessed the evolution of sleep parameters under LCIG infusion over time and the effects on sleep quality. Results Significant improvement following LCIG was observed in PSQI total score (p = 0.007), SCOPA-SLEEP total score (p = 0.008), SCOPA-NS subscale (p = 0.007), and AIS total score (p = 0.001) at 6 months and 1 year, compared to the baseline. The PSQI total score at 6 months correlated significantly with the Parkinson's Disease Sleep Scale, version 2 (PDSS-2) “disturbed sleep” item at 6 months (p = 0.28; R = 0.688), while the PSQI total score at 12 months significantly correlated with the PDSS-2 total score at 1 year (p = 0.025, R = 0.697) and with the AIS total score at 1 year (p = 0.015, R = 0.739). Conclusion LCIG infusion demonstrated beneficial effects on sleep parameters and sleep quality, which were constant over time for up to 12 months.